THE ROLE AND SIGNIFICANCE OF MODERN COMPUTER TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF HEART DISEASES IN ADOLESCENTS AND YOUNG CHILDREN - Sanjarbek Anvarovich Atakhanov; Umida Nabijon qizi Yoqubjonova (Bright Mind Publishing, 2025)
This article presents a detailed analysis of heart diseases common among children and adolescents, the use of modern computer technologies in their diagnosis and treatment, the diagnostic systems developed based on artificial intelligence, and their effectiveness.
Keywords: Congenital heart defects, arrhythmia, myocarditis, hypertension, rheumatic heart diseases, heart failure, ECG analysis, echocardiography, CT scan, MRI, telemedicine, remote ECG monitoring, virtual consultations, hypertension.